Waldensians - Wainmayer, Marcel Gonnet (Italy, Argentina, Brazil, USA, Uruguay, 2016)
The recovery of a silent feature film from 1924, banned by the Italian fascism, reveals the path of the Waldensians, a medieval heretic movement that became the world's first protestant church. The documentary links reality and representation between the medieval Waldensians and actual communities with different languages in Italy, Argentina, Uruguay and the United States.
Keywords: Documentary films